SŪRAH AL-AR’ÁF: LESSONS FOR MULSIM BUSINESS LEADERS - Rodrigue Fontaine (Journal of Islamic Management Studies, 2022)
This study is part of a project that started in 2017. The project consists at looking at specific sūrahs of the Qur’an and extracting lessons for Muslim business leaders. The current study focuses on sūrah al-Ar’af. Two major themes that emerge from this sūrah are the problem of heedlessness and arrogance. Both are diseases of the heart. The sūrah explains in some detail the attacks of satan and how previous nations fell into this trap. Apart from summarizing the main lessons of this sūrah, the author asked his MBA and management students to explore its relevance in the workplace. Their results show that 49% of respondents were concerned with the problem of heedlessness and 44% were concerned with the attacks of satan. The study discusses the results and highlights the lessons for Muslim business leaders.